A unified design approach for control integrating processes with time delay - Yin, Chengqiang; Wang, Shourui; Gao, Jie (PloS one, 2024)
The article presents a unified control system designing scheme to obtain enhanced performance for processes including integrator and dead time. A simple control structure including two controllers is proposed. Servo performance and disturbance rejection performance can be adjusted independently by introducing a desired transfer function model in the control structure. Servo controller is designed according to the direct synthesis principle and disturbance rejection controller is derived adopting the internal model control (IMC) theory. Simulations have been conducted on four kinds of integrating plants with dead time. The simulation results exhibit that noteworthy enhancement can be achieved by the presented scheme in comparation with the other methods even though there are perturbed dynamics.